Managing Zakat Funds Using the DEA Method: Baznas Sumut Efficiency Analysis - Dermawan, Ferry; Samri Juliaty Nasution, Yenni; Harmain, Hendra (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
This study aims to determine the efficiency level of the North Sumatra National Amil Zakat Agency (BAZNAS) in managing zakat funds for the period 2018 to 2022 using the Data Envelopment Analysis (DEA) method with a production approach. The research method uses non-parametric quantitative and collects data by means of documentation. The type of data used is secondary data in the form of financial report data from BAZNAS North Sumatra for the period 2018 to 2022. There are two variables in this study, namely input and output variables. The input variables used are accumulated funds, fixed assets, managed assets, and amiil salaries. While the output variable consists of channeled funds and operational costs. This study uses 2 assumptions, namely Constant Return To Scale (CRS) and Variable Return to Scale (VRS). Based on the results of research conducted using the Data Envelopment Analysis (DEA) method, it was found that BAZNAS North Sumatra managed zakat for the 2018 to 2022 period: In 2018, 2019, and 2020 there were inefficiencies. that is, with numbers 90.29% (2018), 77.37% (2019), and 64.49% (2020). Inefficiency occurs because the actual value is not equal to the target value set by the DEA. Meanwhile, in 2021 and 2022 BAZNAS North Sumatra will be efficient. Because the actual value is the same as the target value determined by the DEA.